Clinical characteristics and immunotherapy response in paraneoplastic neurologic syndrome patients with increased number of high-risk antibodies - Wang, Gong; Chen, Mao; Gao, Fei; Guo, Meng; Li, Maohua; He, Qian; Jiang, Jiaojin; Huang, Cheng; Chen, Xiaoyan; Xu, Rui (Frontiers in Immunology, 2025)
ObjectiveTo investigate the differences of clinical characteristics and treatment outcomes between paraneoplastic neurologic syndrome (PNS) patients with one high-risk antibody and patients with two high-risk antibodies.MethodsWe retrospectively analyzed the data of 51 PNS patients with high-risk antibody. Clinical data were extracted from the patients’ electronic medical records. Clinical presentations, cerebrospinal fluid (CSF) parameters, radiological characteristics and treatment outcomes between patients with one high-risk antibody and patients with two high-risk antibodies were analyzed.Results41 patients with 1 high-risk antibody and 10 patients with 2 high-risk antibodies were enrolled in this study. It was found that psychobehavioral abnormality (OR = 11.327, 95% CI: 1.371 to 93.602, P = 0.024), bowel and bladder dysfunction (OR = 23.537, 95% CI: 1.753 to 316.005, P = 0.017), and total protein of CSF (OR = 61.556, 95% CI: 2.926 to 1294.974, P = 0.008) were risk factors for increased number of high-risk antibodies in PNS. After immunotherapy treatment, Expanded Disability Status Scale (EDSS) scores in PNS patients with 2 high-risk antibodies were higher than that in PNS patients with 1 high-risk antibody (4.8 ± 2.4 vs. 3.0 ± 2.4, p = 0.043). EDSS change analysis also revealed that average EDSS score decreased after treatment in PNS with 1 Ab group while increased in PNS with 2 Abs group (p = 0.032).ConclusionsPsychobehavioral abnormality, bowel and bladder dysfunction, and total protein of CSF were three variables associated with increased number of high-risk antibodies in PNS patients, while increased number of high-risk antibodies might indicate a poor immunotherapy response. Our findings might help to understand the association of PNS patients’ clinical features and high-risk antibodies, as well as to guide clinical practice.